The Relationship Between Islamic Corporate Governance, Human Governance, Usage of Information Technology and Sustainability Reporting: Comparison of Shariah Compliant Companies in Malaysia and Indonesia. - Dato' Hasnah Hj Haron; Nathasa Mazna Ramli; Nurul Nazlia Jamil; Idris Gautama So; Anderes Gui; Synthia Atas Sari (UNIMAS Publisher, 2024)
Indexed by Scopus/MyCite